2020
DOI: 10.26480/asm.01.2021.36.40
|View full text |Cite
|
Sign up to set email alerts
|

Weather Parameters Affecting the Population Dynamics of Leaf Folder and Pod Borers on Mungbean

Abstract: The experiment was conducted to know the abundance of major insect pests on 15 mungbean varieties viz., BARI Mung-1, BARI Mung-2, BARI Mung-3, BARI Mung-4, BARI Mung-5, BARI Mung-6, BINA Moog-4, BINA Moog-5, BINA Moog-6, BINA Moog-7, BINA Moog-8, BU Mug-1, BU Mug-2, BU Mug-4 and Patuakhali local Mung and the role of weather parameters on the population mobility of insects at the farmer’s field of sadar upazila of Patuakhali district, Bangladesh during late Robi season 2016. Variety BARI Mung-4 had the lowest n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The findings of the present study agree with the results of Islam et al (2021) where they stated that varieties did not show complete resistance against major insect pests of mungbean. Our results are also in comparison to work of the previous researchers (Sahoo and Hota, 1991;Naqvi et al 1995;Yadav and Dahiya, 2000;Singh and Singh, 2014) who reported that the findings regarding screening of mungbean cultivars against sucking pets are in the line of the results that we have attained in our study.…”
Section: Mean Number Of Flea Beetle Aphid and Pod Borer Per Plant On ...supporting
confidence: 91%
“…The findings of the present study agree with the results of Islam et al (2021) where they stated that varieties did not show complete resistance against major insect pests of mungbean. Our results are also in comparison to work of the previous researchers (Sahoo and Hota, 1991;Naqvi et al 1995;Yadav and Dahiya, 2000;Singh and Singh, 2014) who reported that the findings regarding screening of mungbean cultivars against sucking pets are in the line of the results that we have attained in our study.…”
Section: Mean Number Of Flea Beetle Aphid and Pod Borer Per Plant On ...supporting
confidence: 91%
“…In addition, it has the ability to fix atmospheric nitrogen (58-109 kg/ha) in symbiotic association with Rhizobium bacteria, which not only covers its own needs, but also promotes subsequent cereal crops in various cultivation systems, thus enriching soil fertility (Anjum et al, 2006;Pratap et al, 2013). However, there are many limitations to its low yield, insect pests are considered important (Islam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%